Recombinant zoster vaccine in immunocompetent and immunocompromised adults: A review of clinical studies - Agnes Mwakingwe-Omari; Nicolas Lecrenier; Abdi Naficy; Desmond Curran; Inga Posiuniene (Human Vaccines & Immunotherapeutics)
Herpes zoster (HZ) is a debilitating vaccine-preventable disease. Impairment of cell-mediated immunity, as observed with aging and immunosuppressive disorders and therapies, increases risk. Recombinant zoster vaccine (RZV) is efficacious against HZ in adults aged ≥50 years in different settings, and in immunocompromised adults aged ≥18 years who are at increased risk of developing HZ. RZV is the first and only HZ vaccine approved for use in immunocompromised adults globally, including in Europe and the US. RZV has a clinically acceptable safety profile and elicits robust immune responses in adults aged ≥50 years, and in immunocompromised adults aged ≥18 years who are at increased risk of HZ. Additionally, RZV is efficacious against HZ complications such as post-herpetic neuralgia and HZ-related pain. This review updates knowledge from a randomized controlled trial setting on the efficacy, safety, immunogenicity, and impact on quality of life of RZV.